Willpower depletion and framing effects - Thomas de Haan; Roel van Veldhuizen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
We investigate whether depleting people's cognitive resources (or willpower) affects the degree to which they are susceptible to framing effects. Recent research in social psychology and economics has suggested that willpower is a resource that can be temporarily depleted and that a depleted level of willpower is associated with self-control problems in a variety of contexts. In this study, we extend the willpower depletion paradigm to framing effects and argue that willpower depletion should increase framing effects. To test this we designed two experiments in which we depleted participants' willpower and subsequently had them take part in a series of tasks, including a framed prisoner's dilemma, an attraction effect task, a compromise effect task, and an anchoring task. However, we find no evidence that framing effects were indeed more prevalent in willpower-depleted participants than in controls.
Keywords: D81; C91; 330; willpower; ego depletion; framing; willpower depletion; experiment; behavioral economics